Korupsi Kredit Perbankan pada PT Sritex: Studi Kasus Penyalahgunaan Wewenang dan Kerugian Negara - Hablana Rizka Nuril Anam; Rahmalia Irmawati; Rista Anindya Wiliyanti; Hastanti Agustin Rahayu (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This research aims to analyze the modus operandi of corruption in bank lending at PT Sri Rejeki Isman Tbk (Sritex), examine the impact of abuse of authority on state losses, and provide recommendations for improving the credit supervision and governance system. The research method used a qualitative descriptive approach with secondary data obtained from reports from the Attorney General's Office, BPK, OJK, and credible media. The results of the study show that the modes of corruption include document manipulation, fictitious credit, collusion between bank officials and debtors, and the acceptance of bribes and gratuities. The impacts include state losses amounting to Rp1.08 trillion, a decline in the reputation of financial institutions, and social impacts such as mass layoffs. The study recommends strengthening internal and external supervision, implementing a blockchain-based digital verification system, and improving the ethics and compliance of bank officials.